2010
DOI: 10.1111/j.1365-2516.2010.02212.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute myocardial infarction in a Chinese patient with haemophilia A and risk factors for coronary artery disease: a case report with autopsy

Abstract: However, due to the possibility of further bleeding, FEIBA was administered FEIBA was administered every 12 h in doses of 100 U kg )1 for 3 days and then every 24 h for 4 days, but we decided not to operate. On day 4, the patientÕs condition improved. During the next few days, the amount of fluid in the left lung decreased. From day 16, rehabilitation was started and FEIBA was administered prophylactically for 2 weeks. The patient was discharged from hospital 6 weeks after the episode and FVIII inhibitor level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The same is true for the patients with FVII deficiency and thrombosis . Only new cases together with exceptional reports which had escaped our previous inquiries are referenced in this article . However, the calculations were carried out on the entire pool of patients.…”
Section: Methodsmentioning
confidence: 99%
“…The same is true for the patients with FVII deficiency and thrombosis . Only new cases together with exceptional reports which had escaped our previous inquiries are referenced in this article . However, the calculations were carried out on the entire pool of patients.…”
Section: Methodsmentioning
confidence: 99%
“… 26 Chest pain syndromes may indicate myocardial ischemia in PWH, especially in those PWH with cardiovascular risk factors or when pain occurs after administration of factor replacement or bypassing agents. 79 …”
Section: General Principles In the Management Of Cardiovascular Diseamentioning
confidence: 99%
“…In China, it is estimated that there are 60,000 to 130,000 patients with hemophilia, [36] but only 4 cases have been recorded. Guo Yang et al [37] reported the first case of a hemophiliac patient who died after suffering from STEMI without receiving antithrombotic or PCI therapy. In 2016, 2 cases were reported in which patients with unstable angina underwent PCI and postoperative antithrombotic therapy without significant complications.…”
Section: Revascularizationmentioning
confidence: 99%